Family Financial Socialization and Its Impact on Financial Decision-Making: A Systematic Review Key Behavioral Theories - Rohmawati, Lilik; Made Laksmi Sena Hartini; Alvionia Filda Sari Mareta; Tri Nurul Khomidah (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study examines the influence of family financial socialization on the financial behavior of the younger generation by exploring both direct and indirect mechanisms through which parents shape financial outcomes. While prior studies have largely focused on explicit parental instruction and implicit role modeling, this research provides a more comprehensive analysis by incorporating psychological and social factors that mediate this relationship. A systematic literature review was conducted on 39 peer-reviewed articles published in reputable journals, employing a structured screening and analysis process. The findings reveal that family financial socialization significantly affects young adults’ financial literacy, attitudes, and behavioral patterns. Both explicit practices, such as financial guidance and discussions, and implicit practices, including observational learning, play a critical role in shaping responsible financial behavior. Moreover, psychological factors, such as self-control, financial attitudes, and risk perception, were found to moderate the relationship between family financial socialization and financial decision-making. These results highlight the importance of family-based financial education in promoting sustainable financial behavior among young adults.